Relación que existe entre el nivel de conocimiento y la aplicación de protocolos de aspiración de secreciones Por Tet en la unidad de cuidados intensivos del Hospital Guillermo Almenara Irigoyen, 2009 - Arpasi Quispe, Orfelina (2019)
Objective: To determine the relationship between the level of knowledge and application of the suctioning protocolof secretions in the Intensive Care Unit at the Guillermo Almenara Irigoyen General Hospital. Methodology: Thetype of study is descriptive, cross correlational. A survey was applied to determine the level of suctioning protocolknowledge and to assess their application by the nurses of the Intensive Care Unit. An observation guide was appliedto a total of 43 nurses. The statistical correlation was performed through the chi square. Results: Of the nurses evaluated both in knowledge and application of the protocol (43) 58.1% have knowledge between good and excellent,while 53.5% have a bad level in the application of the suctioning protocol of secretion. The correlation by chi-squaretest shows a significance of 0.5. Conclusions: The level of knowledge does not correlate with the implementationof the suctioning protocol of secretions.